Local development of Italian voluntary organizations - Barbara Moreschi; Nereo Zamaro (European Regional Science Association (ERSA), 2001)
The aim of the paper is to present some of the results from Istat second survey on voluntary organizations, focusing on the analysis of the heterogeneity among and within them. Data shows that in 1997, in Italy, there were almost 12 thousand voluntary organizations. The majority of them (59.9%) work in the North of the country and there are only four regions collecting more than 50% of the whole universe. Besides territorial differences there are also structural differences among organizations: about 50 percent are members of larger groups, a third are old organizations and most (49.7%) work with a very little number of volunteers (less than twenty).Regarding their economic size, about 50 percent have an income of less than 20 million lire (10,329 euro). Volunteers operating within these organizations are almost 6 hundred thousand and the majority are men (57.4%). Involvment of volunteers is concentrated in their middle ages (45.1% of the volunteers are between 30 and 54), most are employed people (48.2%) and their level of education is not very high (only 11% of the volunteers have a university degree). Most of the Italian voluntary organizations operate in Health (37.6%) and Social Protection (28.7%), while the others work in sectors like Recreation Activities, Emergency and Relief, Environment, Education, Advocacy, Sport Activities and Culture. Within this framework some statistical methods are applied to illustrate organizational diversity within the population of italian voluntary organizations. Even in this homogeneous subset of nonprofit institutions the relationships and processes out of which facilities and networks are produced vary, being influenced by organizational charateristics instead of territorial differences.
Keywords: 330